Education for whom and why? Managing the educational process of senior citizens - Kaczmarek, Żanetta (Horyzonty Wychowania, 2019)
RESEARCH OBJECTIVE: Determine student programme preferences in the context of a diagnosis of their behaviour in terms of maintaining good health. THE RESEARCH PROBLEM AND METHODS: How may the educational process be organized? What programme content do students expect? What behaviour, in terms of maintaining good health, do they exhibit? Methods: diagnostic survey, narrative interview, observation. THE PROCESS OF ARGUMENTATION: It is demanded of our civilization that we engage in lifelong learning. The process of educating senior citizens demands diagnostic research, with a concern for its effects. REASERCH RESULTS: The optimalization and management of the educational process: preparing an instructional programme with effective content and methods. CONCLUSION, INNOVATIONS, AND RECOMMENDATIONS: the programme should facilitate the participation of the community and prepare people to anticipate events; intergenerational cooperation is recommended.